Study on Performance and Emission of Diesel Engine Using Palm Oil Biofuel-Diesel Blends - Asnawi Asnawi; Muhammad Muhammad; Abdul Rahman; Nurul Islami (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
The addition of biofuel to diesel increases the fuel's stability, density, viscosity, energy content, and cetane number Blending biodiesel and diesel improves the viscosity of the combined fuel in comparison to diesel fuel. Recently, studies on optimizing the use of biodiesel diesel fuel have begun to examine the effects on diesel engine components and the energy conversion efficiency of biodiesel fuel use. The addition of supplements from other natural fuels is an effective option to improve energy conversion efficiency, but the blending effect causes changes in fuel properties. Therefore, further analysis is needed to meet the fuel standards used in diesel engines. This study is to obtain a clearer analysis of the effect of biofuel addition on diesel engine performance and exhaust emissions. Measurements of experiment variables such as Torque, thermal efficiency, power, bsfc, and gas emission obtained from sensors installed in each part of the laboratory scale of diesel engine. The result shows blends of biofuel and diesel can be used as alternative fuels in conventional diesel engines. The variation of power generated by both of fuel mixture shows average power without any major changes. The thermal efficiency of 30% biofuel average is better across all engine speed variations whereas the carbon monoxide variation decreases towards the same amount at 3000 rpm.